Toward an Optimum Yield: Science, Technology, and Fisheries Development in Lake Malawi, 1930–1964. - Wilson, David; Gough, Milo; Nkhoma, Bryson; Chirwa, Elias; Knapp, Charles W.; Morse, Tracy; Mulwafu, Wapulumuka (Isis: A Journal of the History of Science in Society, 2026)
In the late colonial period, fisheries science and colonial development programs converged in blueprints to better exploit marine resources throughout the British empire. Yet, the historiography of science and colonial development has focused predominantly on the management and exploitation of terrestrial resources with only limited investigation of parallel schemes focused on marine and freshwater resources. Centering on the final decades of the British-ruled Nyasaland Protectorate, this article interrogates the role of science in shaping the regulations and development of Lake Malawi's fisheries. It argues that the late-colonial fusion of scientific optimization and legislative frameworks tethered government-led fisheries development programs to a vision of optimal resource extraction, governmental custodianship, and technical development that was entrenched in a faith in scientific management but without the necessary data to monitor changes in fishing efforts or the capacity to enforce fishing regulations. Consequently, scientists' recommendations helped to embed assumptions of custodianship and control over watery environments within legislative frameworks that were increasingly disconnected from the evolving commercial, environmental, and technological contexts shaping Indigenous-led and settler-owned fishing enterprises.